JUDICIAL CONSIDERATION IN GRANTING A FOURTH WIFE PERMIT: A MAQĀṢID AL- SHARĪ'AH PERSPECTIVE ON THE DECISION OF THE RELIGIOUS COURT OF MALANG - Rekak, Nurlailatul Badriyyah; Stiawan, Thoat; Al-Farisi, Salman; Ikhwanuddin, Mohammad; Berkah, Dian (istinbath, 2025)
The practice of polygamy, especially in the form of marriage applications for fourth wives, still raises legal and ethical debates in Indonesian society. The Malang City Religious Court Decision Number 1471/Pdt.G/2024/PA.MLG is an interesting case. Which granted the application. This study aims to analyze the judge's reasoning in the decision through the perspective of Maqāṣid al- Sharī'ah according to Imam al-Syāṭibī, to evaluate the extent to which the decision is in line with the five main objectives of the Shari'ah (al-kulliyyāt al-khamsah). The research method used is qualitative with a normative juridical approach, focusing on analyzing legal documents, court decisions, and relevant literature. The results showed that although the petition was granted formally, not all aspects of maqāṣid, such as the protection of the soul (ḥifẓ al-nafs), offspring (ḥifẓ al- nasl), and property (ḥifẓ al-māl) were fulfilled thoroughly. The application of maqāṣid is still partial and tends toward administrative justification. The implications of this finding emphasize the importance of comprehensively strengthening the maqāṣid al-shari'ah approach in family law considerations so that the policies taken are not only legally valid but also reflect the value of justice and substantial benefit as the main objectives of Islamic law.